1980
DOI: 10.1097/00003086-198001000-00005
|View full text |Cite
|
Sign up to set email alerts
|

The Rationale of Functional Bracing of Fractures

Abstract: Fracture bracing is a philosophy rather than merely the use of orthotic devices in the treatment of fractures. It is predicated on the belief that immobilization of the fragments and the joints above and below the fracture is not necessary for fracture healing. It proposes also that the soft tissues of the injured extremity play a major role in providing the stability necessary to allow uninterrupted osteogenesis.The encouraged early function, weightbearing and motion of the joints and fracture fragments durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
0
4

Year Published

1988
1988
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 2 publications
1
33
0
4
Order By: Relevance
“…Latta and coworkers [11] and Sarmiento and co-workers [17] noted that controlled movement at the fracture site is conductive for osteogenesis. In recent years, important studies have been published comparing plating and intramedullary nailing of the humeral shaft [3,6] but the role and justification of conservative treatment has not been called into question [10,19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Latta and coworkers [11] and Sarmiento and co-workers [17] noted that controlled movement at the fracture site is conductive for osteogenesis. In recent years, important studies have been published comparing plating and intramedullary nailing of the humeral shaft [3,6] but the role and justification of conservative treatment has not been called into question [10,19].…”
Section: Discussionmentioning
confidence: 99%
“…However, not all humeral shaft fractures are eligible for conservative treatment. Absolute and relative indications for surgical treatment have been described [1,11] (Table 1). Plaster splint, hanging cast and sugar tong splint were formerly used in conservative treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The energy-absorbing capacity of the callus with soft tissues was doubled by muscle contraction. Latta et al (1980) found that the soft tissues carried over 80 percent of the load when they instrumented fracture braces on patients with fresh fractures of the tibia and fibula. Sarmiento et al (1974) and Latta et al (1980) concluded from their experiments that the brace and the soft tissues acted together as a hydraulic cylinder, which gave strength and stability to the fracture.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that early motion enhances osteogenesis, promotes revascularization of the damaged tissue, and improves the biological healing process (Latta et al 1980, Sarmiento andLatta 1981). Many studies have shown a difference in the functional result after fractures and joint injuries between plaster cast immobilization and functional splints that was in favor of the splints, especially in terms of the earlier normalization of strength and range of motion (Sarmiento et al 1975, Arafa et al 1986, deBruijn 1987, Abbaszadegan et al 1989.…”
Section: Discussionmentioning
confidence: 99%